Chocolates Effect on Cardiovascular System - Surja, Sem Samuel; Krisanti, Stefani; Ariwibowo, Hendrawan (The Journal of The Indonesian Medical Students Association, 2010)
Chocolate is one of the most common foods which many people consume. Chocolate has many effects to human health, one of which is for cardiovascular system. Some rumors say that chocolate has deteriorating effect for cardiovascular system because of its high fat content. On the other hand, the levels of antioxidants in chocolate said to have a positive effect on cardiovascular system. This paper discusses more about the cardiovascular effects of chocolate. Various literatures starting from year 2003 to 2008 related to the topic is collected to support the writing of this paper. From the results of this literature review, it was found that consumption of chocolate can provide short-term improvement on endothelial function and reduction in systolic and diastolic blood pressure. Other effects such as effects on fat profiles and pulse are still controversial. Underlying component of chocolate that contribute to these effects is flavanoid. Another component of chocolate feared to have deteriorating effect is stearic acid, that may increase blood cholesterol, but it is still not proven in various studies. Author concludes that chocolate has positive short-term effects for cardiovascular system. But because of the limitations of the various studies, long-term effects of chocolate consumption are still not known with certainty. Type of chocolate that was considered as the most useful for cardiovascular system is high-flavanoid content dark chocolate.ÃÂ Key words: chocolate, cardiovascular system, flavanoids, endothelial function, blood pressure